Johnny got his gun - Trumbo, Dalton, 1905-1976. (New York : Bantam, 1982)
A young man who was severely wounded in World War One thinks about his life and about the horror and futility of war and its toll on him.
"Bantam Windstone.".
Wilson's Fiction.
Wilson's Senior High School.
Adult
Keywords: World War, 1914-1918 -- Fiction; Young men -- Fiction; War stories; World War, 1914-1918 -- Fiction; Young men -- Fiction